Memoing for Conceptual Emergence - Astrid Gynnild (Grounded Theory Review: An International Journal, 2025)
When doing grounded theory, writing starts in the moment you begin the study. Daily writing is integrated into the method itself, and the key concepts are memos and memo writing, and, in grounded theory terminology, memoing. Memos form the textual fundament for theory building and are sorted and refined as the project moves along. In this article, I will explore how memoing in classic grounded theory provides space for reflexivity that is crucial to a researcher´s personal growth. The discussion is based on the original literature written by Barney G. Glaser and on memos and field notes from participant observation in Glaser´s troubleshooting seminars over the first two decades of the 21st century.